The class II phosphatidylinositol 3 kinase C2beta is required for the activation of the K+ channel KCa3.1 and CD4 T-cells. - Srivastava, S; Di, L; Zhdanova, O; Li, Z; Vardhana, S; Wan, Q; Yan, Y; Varma, R; Backer, J; Wulff, H; Dustin, M; Skolnik, E (2009)
The Ca(2+)-activated K(+) channel KCa3.1 is required for Ca(2+) influx and the subsequent activation of T-cells. We previously showed that nucleoside diphosphate kinase beta (NDPK-B), a mammalian histidine kinase, directly phosphorylates and activates KCa3.1 and is required for the activation of human CD4 T lymphocytes. We now show that the class II phosphatidylinositol 3 kinase C2beta (PI3K-C2beta) is activated by the T-cell receptor (TCR) and functions upstream of NDPK-B to activate KCa3.1 channel activity. Decreased expression of PI3K-C2beta by siRNA in human CD4 T-cells resulted in inhibition of KCa3.1 channel activity. The inhibition was due to decreased phosphatidylinositol 3-phosphate [PI(3)P] because dialyzing PI3K-C2beta siRNA-treated T-cells with PI(3)P rescued KCa3.1 channel activity. Moreover, overexpression of PI3K-C2beta in KCa3.1-transfected Jurkat T-cells led to increased TCR-stimulated activation of KCa3.1 and Ca(2+) influx, whereas silencing of PI3K-C2beta inhibited both responses. Using total internal reflection fluorescence microscopy and planar lipid bilayers, we found that PI3K-C2beta colocalized with Zap70 and the TCR in peripheral microclusters in the immunological synapse. This is the first demonstration that a class II PI3K plays a critical role in T-cell activation.